Together we can stop the bomb (CND (Campaign for Nuclear Disarmament), 1981)
High contrast, red and white photograph of crowd demonstrating, holding signs with peace symbols Poster advertising campaign and calling rally against nuclear weapons, held in London, 24 October, 1981 PO-1620